1980
DOI: 10.1152/ajprenal.1980.239.6.f560
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and collecting duct intramembranous particle clusters: a dose-response relationship

Abstract: Vasopressin increases the permeability of collecting ducts to water. Administration of this hormone is also associated with an increase in intramembranous particle clusters in rat collecting duct luminal membrane (CDLM) as revealed by freeze-fracture electron microscopy. To determine whether this morphologic alteration of CDLM is quantitatively related to the dose of vasopressin, anesthetized Brattleboro homozygous rats were given the hormone at different doses. CDLM from kidneys removed before and during infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 0 publications
3
28
0
1
Order By: Relevance
“…However, as shown in Figs. 10 and 11, inhibition of membrane retrieval is not produced solely by exposure to cold, but also occurs when transepithelial water flow is reduced to below an apparent threshold. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as shown in Figs. 10 and 11, inhibition of membrane retrieval is not produced solely by exposure to cold, but also occurs when transepithelial water flow is reduced to below an apparent threshold. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence indicates that particle aggregates are closely correlated with or are themselves water channels responsible for the increase in apical membrane water permeability induced by ADH (reviews 8, 9). Freeze-fracture electron microscopy has also revealed that distinctive intramembrane particle structures are closely correlated with ADHinduced permeability changes in the apical membrane of the mammalian collecting duct (10)(11)(12).…”
Section: Introductionmentioning
confidence: 97%
“…When ADH is withdrawn, particle aggregates and aggrephores are retrieved from the apical membrane (9,10), and the water permeability response reverses. The particle aggregates are intimately involved in water permeability (11)(12)(13)(14) and they may well be the site of specific water channels (reviewed in refs. 15 and 16).…”
mentioning
confidence: 99%
“…On the basis of earlier evidence from amphibian model systems, isolated perfused collecting ducts, and in vivo studies, it was proposed that VP acted by stimulating water channel insertion into the apical plasma membrane by VP-induced exocytosis of cytoplasmic vesicles (29,45,48,57,100,141). While a modeling study in 1993 proposed that both the exocytotic and the endocytotic arms of the pathway were likely to be involved in the process leading to membrane accumulation of water channels (64), most attention was focused on the exocytotic pathway as the main regulatory event in the onset of VP action (141).…”
Section: Role Of Both Exocytosis and Endocytosis In Aqp2 Membrane Accmentioning
confidence: 99%